France - Skorupska, Adriana (The Role of Regions in EU-China Relations, 2021)
The main objective of this chapter is to characterise the activities between French regions and Chinese provinces or cities – their intensity, scopes, advantages and obstacles. Besides, as the context for the paradiplomacy, a broader perspective is briefly introduced focusing on the bilateral state, economic and social relations. An important question arises as to whether the relations at the state level correlate with the relations at the lower, regional, level. Taking the broader perspective into account, it is worth evaluating how the EU-China relation and the internal situation of China influence paradiplomacy.